(untitled) (Annals of Medical Research, 2021)
Aim: The clinical features of epidermal cyst (EC) are well known, however, dermoscopic aspect of the entity has rarely been a subject of investigation. Here we aimed to identify the dermoscopic findings of EC which may increase the accuracy of diagnosis before surgical interventions. Material and Methods: The study included the patients diagnosed with EC those who applied to outpatient dermatology clinic of a tertiary center. Age and gender of the patients, disease durations, symptoms, site and size of the lesions, dermoscopic and histopathological findings were retrospectively reviewed. Results: A total of 24 lesions from 24 patients were enrolled in the study. The most common dermoscopic finding was white structureless background (96%) followed by punctum/pore sign (75%), widely distributed/branched irregular linear vessels (71%), blue-white structureless color (46%), mobility sign (41%), peripheral thick branched vessel (33%) and polychromatic structures (4%).Conclusion: We describe two novel dermoscopic features which were not described previously for EC: Mobility sign and polychromatic structures. Along with the previous studies, our study revealed that EC has a peculiar dermoscopic pattern. Dermoscopic examination may increase diagnostic accuracy before surgery making possible a management with minimal invasive procedures.Keywords: Dermatoscopy; dermoscop; epidermal cyst.